Families transition, too! Military families transition out of service: a scoping review of research from the Five Eyes nations. Issue 4 (20th October 2022) - Dodge, Jessica; Kale, Caroline; Keeling, Mary; Gribble, Rachael; Taylor-Beirne, Sean; Maher, Stephen; Castro, Carl; Fear, Nicola T; Sullivan, Kathrine
ABSTRACT: There is minimal research about the military-to-civilian transition (MCT) from the perspective of the family. The goal of this scoping review was to identify what is known about military families across the Five Eyes Nations (FVEY) (Australia, Canada, New Zealand, the United Kingdom, and the United States) during this phase as well as identify gaps in the evidence base. Scoping review methods were employed with a narrative review process to conceptualize and organize results. The initial search returned 2, 219 sources. From these, 27 sources about military family experiences during MCT were identified. Overall, there was limited research on this topic with the majority of sources being from gray literature. A contributing factor to this lack of literature could be the conflation of the MCT with other military transitions (i.e. deployments). Sources highlighted four major themes that influenced identified needs and current services for military families during MCT: (1) mental health; (2) barriers to care; (3) financial needs; and (4) targeted transition support. The limited literature documents promising family skills-based interventions during MCT. However, there is a need for more empirical research on existing family-based interventions and experiences and needs of the family as a unit during MCT.